CLASSROOM TECHNIQUES USED IN THE TEACHING OF ENGLISH BASED ON CURRICULUM 2013: A NATURALISTIC STUDY AT STATE JUNIOR HIGH SCHOOL OF SAWIT 1 BOYOLALI - Umi Nur Kurniliawati (Jurnal Penelitian Humaniora, 2016)
This study is carried out to describe classroom technique used in the teaching of English at State of Junior High School of Sawit 1 Boyolali. The kinds of this research is describtive qualitative research especially naturalistic study in analyzing the data. The method of collecting data in this research are observation, interview and document. The finding of the study shows that there are some classroom techniques implemented by English teachers at SMP Negeri 1 State of Junior High School of Sawit 1 Boyolali, drilling, grouping, individual task, listening to music, picture describing, presentation, question and answer, questioning, reading aloud, repetition, role play, and translation.The teachers have roles as facilitator, teacher as motivator, teacheras observer, teacher as manager, teacher as model, teacher as counselor, teacher as controller, and teacher as evaluator. The students have roles as members of group, as tutor of other learners, as negotiator, as subject, and as monitor and evaluator of their own learning progress. There are some materials used by English teachers, such as: textbook, workbook, dictionary, photocopy exercises, powerpoint on LCD, audio like song, and videos from youtube. The conclusion of this research is that English teachers at State of Junior High School of Sawit 1 Boyolali used various classroom techniques which can improve the students’ ability. Various techniques can make the students interested in English teaching-learning process. It does not make the class monotonous. The students become more active and creative. Based on the results, apparently, classroom techniques used by the teachers have important role in the teaching-learning process.